Teams Games Tournament for Computational Thinking Outcomes at SMP St. Yoseph Pemuda Medan - Theresia Shintanauli Margaretha Silalahi (Jurnal Pendidikan, Media, Strategi, dan Metode., 2026)
Computational thinking is an important topic in junior high school Informatics because it helps students solve problems through decomposition, pattern recognition, abstraction, algorithmic thinking, and debugging. However, students may experience difficulty understanding computational thinking when learning is delivered mainly through conventional explanation and individual exercises. This study investigated the effect of the Teams Games Tournament learning model on students’ learning outcomes in computational thinking material at SMP St. Yoseph Pemuda Medan. The study employed a quasi-experimental pretest-posttest control group design. The sample consisted of 60 students divided into an experimental group and a control group, with 30 students in each group. The experimental group learned through the Teams Games Tournament model, while the control group learned through conventional instruction. Data were collected using a 25-item computational thinking achievement test scored on a scale of 0 to 100. The data were analyzed using descriptive statistics, N-Gain, paired-sample t-test, independent-sample t-test, and effect size analysis. The findings showed that the experimental group improved from a pretest mean of 53.47 to a posttest mean of 81.90, with a mean gain of 28.43 and a mean N-Gain of 0.62. The control group improved from a pretest mean of 53.00 to a posttest mean of 68.33, with a mean gain of 15.33 and a mean N-Gain of 0.33. The paired-sample t-test showed significant improvement in both groups, p < .001. The independent-sample t-test on posttest scores showed a significant difference in favor of the experimental group, t(57.99) = 12.92, p < .001, with a very large effect size, d = 3.34. The study concludes that Teams Games Tournament is effective in improving students’ Informatics learning outcomes on computational thinking material.